Diabetes and Hepatitis C: A Two-Way Association - Hammerstad, Sara Salehi; Grock, Shira Frankel; Lee, Hanna J.; Hasham, Alia; Sundaram, Nina; Tomer, Yaron (Frontiers in Endocrinology, 2015)
Diabetes and hepatitis C infection are both prevalent diseases worldwide, and are associated with increased morbidity and mortality. Most studies, but not all, have shown that patients with chronic hepatitis C are more prone to develop type 2 diabetes compared to healthy controls, as well as when compared to patients with other liver diseases including hepatitis B. Furthermore, epidemiological studies have revealed that patients with type 2 diabetes may also be at higher risk for worse outcomes of their hepatitis C infection, including reduced rate of sustained virologic response, progression to fibrosis and cirrhosis, and higher risk for development of hepatocellular carcinoma. Moreover, hepatitis C infection and mainly its treatment, interferon α, can trigger the development of type 1 diabetes. In this review we discuss the existing data on this two-way association between diabetes and hepatitis C infection with emphasis on possible mechanisms. It remains to be determined whether the new curative therapies for chronic hepatitis C will improve outcomes in diabetic hepatitis C patients, and conversely whether treatment with Metformin will reduce complications from HCV infection. We propose an algorithm for diabetes screening and follow-up in hepatitis C patients.